Tuberculosis and COVID-19: An overlapping situation during pandemic - KARAHASAN, AYŞEGÜL; OLGUN YILDIZELİ, ŞEHNAZ; SİLİ, ULUHAN (J INFECTION DEVELOPING COUNTRIES, 2020)
Introduction: The novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the coronavirus disease 2019 (COVID-19). First COVID-19 case was detected in March, 10, 2020 in Turkey and as of May, 18, 2020 148,067 cases have been identified and 4096 citizens have died. Tuberculosis (TB) is a worldwide public health concern, incidence of tuberculosis (per 100,000 people) in Turkey was reported at 14, 1 in 2018. During pandemic COVID-19 was the main concern in every clinic and as we discuss here overlapping respiratory diseases may result in delaying of the diagnosis and treatment. Methodology: There were 4605 respiratory samples examined between March 23 and May 18 for COVID-19 and 185 samples for Mycobacterium tuberculosis in our laboratory. The Xpert Ultra assay was performed for the diagnosis of pulmonary tuberculosis; SARS-CoV-2 RNA was determined by real-time PCR (RT-PCR) analysis in combined nasopharyngeal and deep oropharyngeal swabs of suspected cases of COVID-19. Results: Both of SARS-CoV-2 and M. tuberculosis tests were requested on the clinical and radiological grounds in 30 patients. Here we discussed 2 patients who were both COVID-19 and TB positive. One patient already diagnosed with tuberculosis become COVID-19 positive during hospitalization and another patient suspected and treated for COVID-19 received the final diagnosis of pulmonary TB and Human Immunodeficiency Virus infection. Conclusions: We want to emphasize that while considering COVID-19 primarily during these pandemic days, we should not forget one of the great imitators, tuberculosis within differential diagnoses.
Keywords: COVID-19; Mycobacterium tuberculosis; SARS-CoV-2; PCR; HIV